PENERAPAN MODEL TUTORIAL PAT UT-II DALAM PEMBELAJARAN KETERAMPILAN MENULIS NARASI PROGRAM S1 PGSD UPBJJ-UT MAKASSAR - Patmawati, Patmawati (Jurnal Pendidikan, 2010)
The research aimed to identify the effect of applying PAU-UT model on narrative writing skills tutorial session among students of S1 PGSD programme. Through experimental methods, this study involved two group of samples: Group 1 was treated using the PAT-UT 1 model, and Group 2 was treated using PAT-UT 2 model. Data were gathered through questionnaires and tests of narrative/text writing ability and then were analyzed using descriptive statistical tests and t-test. The results on text writing skills using PAT-UT 2 model showed better results compared to PAT-UT 1 model. Result of t-test showed that groups treated with PAT-UT 2 model provides higher learning outcomes than groups treated with PAT-UT 1 model (t.s.0.90 = 1,32). Concluded that the implementation of PAT-UT 2 on narrative writing skills can improve learning activity and learning outcome of students of S-1 PGSD programme.